Kelayakan Finansial Usahatani Buah Naga Di Daerah Perkotaan Sebagai Alternatif Tambahan Pendapatan Petani - IDA AYU LISTIA DEWI; I NYOMAN GEDE USTRIYANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Financial Feasibility Of Dragon Fruits Farming In Urban Area As AdditionalAlternatives Of Farmer’s Revenues This study aims to analyze the financial feasibility of Dragon Fruit Farming in urbanareas. Analyze the sensitivity of Dragon Fruit farming on the changes of productionquantity, product selling price, and production cost. The pilot unit of Dragon FruitFarming in urban area is in Experiment Garden of Faculty of Agriculture UdayanaUniversity. Key informants of this research are garden managers, field officers, fieldworkers in Experimental Garden of Faculty of Agriculture Udayana University. Thedata used are Bank Rakyat Indonesia's interest rate, investment cost (seedlingcuttings, climbers, used tires, rope, and equipment), operational cost (fertilizer andlabor), production quantity, and product selling price. Data analysis used analysis ofinvestment criteria and business sensitivity analysis. The results showed that theDragon Fruit Farming in Experimental Garden of Faculty of Agriculture UdayanaUniversity was profitable so it was feasible to run. The value of farm income is Rp231,453,087, Net B / C value is 4.03. IRR> I is 49.63%> 18%, the rate of paybackfor five years is eight months. This effort is very sensitive to the 50% decline in theselling price.